2023
DOI: 10.1371/journal.ppat.1011210
|View full text |Cite
|
Sign up to set email alerts
|

Same, same but different: Exploring Plasmodium cell division during liver stage development

Abstract: Plasmodium parasites have a complex life cycle alternating between a mosquito and a vertebrate host. Following the bite of an Anopheles female mosquito, Plasmodium sporozoites are transmitted from the skin to the liver; their first place of replication within the host. Successfully invaded sporozoites undergo a massive replication and growth involving asynchronous DNA replication and division that results in the generation of tens of thousands or even hundreds of thousands of merozoites depending on the Plasmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 130 publications
0
11
0
Order By: Relevance
“…During male gametogenesis, the parasite undergoes three rounds of mitosis without nuclear division, creating an 8n nucleus that undergoes combined nuclear and cell division to form eight gametes (Matthews et al, 2018). During liver‐stage replication, merozoites are formed via schizogony (Roques et al, 2023), but the details of mitosis and nuclear division in liver‐stage parasites are not well understood. It has recently been shown that during sporogony in oocysts, large nuclei likely contain multiple genome copies (Araki et al, 2020), but the dynamics of mitosis and nuclear division in this stage of the lifecycle are yet to be elucidated.…”
Section: Expansion Microscopymentioning
confidence: 99%
“…During male gametogenesis, the parasite undergoes three rounds of mitosis without nuclear division, creating an 8n nucleus that undergoes combined nuclear and cell division to form eight gametes (Matthews et al, 2018). During liver‐stage replication, merozoites are formed via schizogony (Roques et al, 2023), but the details of mitosis and nuclear division in liver‐stage parasites are not well understood. It has recently been shown that during sporogony in oocysts, large nuclei likely contain multiple genome copies (Araki et al, 2020), but the dynamics of mitosis and nuclear division in this stage of the lifecycle are yet to be elucidated.…”
Section: Expansion Microscopymentioning
confidence: 99%
“…Similar sub-compartments are present during oocyst development 36 . Based on apicoplast visualizations in P. berghei and our observations of the formation of MOCs during oocyst stages, mitochondrial and apicoplast dynamics in these sub-compartments in both oocyst and liver stages resemble the dynamics of these organelles in blood-stage schizogony 11,37,38 . Although the use of new imaging techniques, such as expansion microscopy and 3D volume EM, have revealed new insights in mitochondrial dynamics, many questions about the timing and organization of mitochondrial division remained unanswered 10,31 .…”
Section: Discussionmentioning
confidence: 68%
“…Plasmodium , the causative agent of malaria, is an alveolate Apicomplexa parasite that exhibits extensive plasticity in mitosis and cell division during its life cycle, with proliferation within the two hosts, the Anopheles mosquito, and a vertebrate. These parasites display some atypical aspects of cell division, for example in terms of cell cycle, MTOC organisation, chromosome segregation and nuclear division, presumably to facilitate genome replication and cell proliferation in the varied environments (Guttery et al, 2022; Roques et al, 2023; Voss et al, 2023). In a mammalian host, asexual division (schizogony) occurs first in hepatocytes followed by cyclic schizogony and replication in erythrocytes (the blood stage); parasites progress through ring, trophozoite and the multinucleate schizont stage, finally releasing merozoites to infect new cells.…”
Section: Introductionmentioning
confidence: 99%